Pengembangan Lembar Kerja Peserta Didik (LKPD) IPA Berbasis Nilai Karakter - Alwi, Mijhamuddin; Suastra, Wayan; Ariana, Ida Bagus (Kappa Journal, 2023)
This study aims at developing teaching materials for Student Worksheets (LKPD) Based on Character Values for fifth graders of SDN 1 Darmasari in the Academic Year 2022/2023. This research is development research with a 4D development model in stages which is simplified into 3 stages, namely, defining, designing, and developing. This research was conducted in the fifth grade of elementary school with 32 students. This development instrument uses validation sheets, and student response questionnaires. The results of the validation of material and language experts with a total score of 58 which are included in the score range of X> 50 in the "very good" category. Meanwhile, the display expert gets a score of 29 which is included in the range X> 25 with the "very good" category. And the results of the student response questionnaire on the effectiveness of the use of teaching materials (LKPD) developed got an average score of 68, which is included in the score range X> 63 with the "very good" category. So, it can be concluded that the development of teaching materials (LKPD) based on character values in science subject in fifth grade of SDN 1 Darmasari is very good and effective for use by students in the learning process.